Range-compensated pencil beam scanning proton Arc therapy: a feasibility study - Blake R. Smith; Ryan T. Flynn; Alonso N. Gutiérrez; Daniel E. Hyer (Communications Engineering)
Abstract Proton arc therapy is a conceptual treatment technique in proton therapy that delivers a scanned proton pencil beam simultaneously as the gantry is rotated around the patient, exploiting the geometric advantages of a continuous arc with the dosimetric advantages of protons to maximize healthy tissue sparing. Here we propose an alternative approach to deliver pencil beam scanning (PBS) proton arc therapy using a beam-modifying device called a SpeleoFilter. SpeleoFilters can improve the treatment efficiency of proton arc by reducing the number of beam energies and beam spots while preserving the plan quality as compared to traditional multifield intensity modulated proton therapy (IMPT). The proposed SpeleoFilter framework was validated within a state-of-the art PBS collimator and IBA Dedicated Nozzle PBS system at the Miami Cancer Institute. The Monte Carlo methods developed in this work showed great agreement with experimental measurements and matched depth dose profiles within a 1–2%/1 mm gamma criteria. Proton arc treatments utilizing a SpeoleFilter resulted in comparable healthy tissue sparing and an order-of-magnitude reduction in the number of energy layers compared to IMPT for both phantom and patient datasets. Further work is necessary to fully demonstrate its application and clinical integration for multiple treatment sites.